2021
DOI: 10.1186/s12870-021-03274-1
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis provides insights into the salt tolerance of Podocarpus macrophyllus under salinity stress

Abstract: Background Soil salinization is causing ecosystem degradation and crop yield reduction worldwide, and elucidation of the mechanism of salt-tolerant plants to improve crop yield is highly significant. Podocarpus macrophyllus is an ancient gymnosperm species with a unique environmental adaptation strategy that may be attributed to its lengthy evolutionary process. The present study investigated the physiological and molecular responses of P. macrophyllus plants to salt stress by analyzing its pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…In Cornus hongkongensis subsp. elegans , Vitis amurensis Rupr, and Podocarpus macrophyllus , salt stress led to disorganized cystoid, basidiome, and stroma lamellae structures, which seriously damaged the integrity of the chloroplast ultrastructure [ 17 , 27 , 73 ]. The results of our experiments showed that the grease content increased as the salt concentration increased.…”
Section: Discussionmentioning
confidence: 99%
“…In Cornus hongkongensis subsp. elegans , Vitis amurensis Rupr, and Podocarpus macrophyllus , salt stress led to disorganized cystoid, basidiome, and stroma lamellae structures, which seriously damaged the integrity of the chloroplast ultrastructure [ 17 , 27 , 73 ]. The results of our experiments showed that the grease content increased as the salt concentration increased.…”
Section: Discussionmentioning
confidence: 99%
“…Plant hormone signal transduction is an essential component of plant stress-response signaling pathways, as the most important endogenous substances, phytohormones play critical roles in stress response and growth promotion [ 55 ]. The transcriptome analysis of Podocarpus macrophyllus indicate that the transcription of genes involved in biosynthesis and phytohormone signaling pathways have been altered significantly, and genes related to auxin transport and responsiveness are downregulated in response to salt stress [ 56 ]. In Chenopodium quinoa , salt stress results in a decrease in signaling components of growth-related phytohormones (auxin, BR) and an increase of components in ABA signaling pathway (PP2Cs), while some other important components of ABA pathway (PYLs, SnRK) are downregulated under long-term salt stress [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…POD (EC1.11.1.7) activity was measured at 470 nm as described in [ 69 ]. CAT (EC1.11.1.6) activity was assayed as described in [ 70 ]. APX (EC1.11.1.11) activity was determined as described by [ 71 ].…”
Section: Methodsmentioning
confidence: 99%